Guided routing on spinning microfluidic platforms - Kazemzadeh, A.; Ganesan, P.; Ibrahim, F.; Kulinsky, L.; Madou, M.J. (Royal Society of Chemistry, 2015)
Flow directionality, valving and liquid routing in centrifugal microfluidics (Lab-on-CD) are typically controlled by applying centrifugal and Coriolis forces and have been the subject of active research interest in recent years. Determining and switching the flow direction at a T-junction is a common fluidic operation important for implementing several chemical and clinical assays for Lab-on-CDs. The present work describes a novel approach to route samples and control flow direction on a spinning disc that employs a guiding microstructure that relies on a two-stage valve comprised of an auxiliary inlet, which is a recess embedded at a T-junction, and a bent auxiliary outlet. The distinctive feature that makes this approach different from other types of passive capillary valves is the strong control of liquid movement, which is achieved by employing two adjustable sequential burst valves called a primary valve and a secondary burst valve. The guiding method can be used to route samples and reagents at given flow rates to a selection of receiving reservoirs, which are determined by the spinning frequency of the disc. The technique also allows for the switching of the flow direction instantaneously from the direction along the disc rotation to the opposite direction by increasing the rotational speed of the disc rather than relying on the Coriolis force, which would require reversing the spin direction. The flow routing by the proposed technique has been studied theoretically, and the flow behavior has been numerically investigated. These studies have been experimentally validated for a wide range of capillary sizes and for various liquids including di-water, mixtures of water and ethanol and bovine serum albumin (BSA).